2014
DOI: 10.1371/journal.pone.0113131
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Clinical Parameters for the Prediction of Urodynamic Bladder Outlet Obstruction: Analysis Using Causal Bayesian Networks

Abstract: PurposeTo identify non-invasive clinical parameters to predict urodynamic bladder outlet obstruction (BOO) in patients with benign prostatic hyperplasia (BPH) using causal Bayesian networks (CBN).Subjects and MethodsFrom October 2004 to August 2013, 1,381 eligible BPH patients with complete data were selected for analysis. The following clinical variables were considered: age, total prostate volume (TPV), transition zone volume (TZV), prostate specific antigen (PSA), maximum flow rate (Qmax), and post-void res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
13
1
4
Order By: Relevance
“…Although our clinical nomogram targets men with refractory LUTS, its accuracy is comparable to that of the previously published nomogram or predictive model in men with treatment-naïve or common LUTS (73.5%–83.2%) 1127. The predictive model proposed by Kim et al 27 was constructed by a combination of Qmax, PVR volume, and TPV. Notably, De Nunzio et al 11 selected only Qmax and transitional zone volume as independent statistical predictors of BOO in the development of their nomogram.…”
Section: Discussionsupporting
confidence: 56%
“…Although our clinical nomogram targets men with refractory LUTS, its accuracy is comparable to that of the previously published nomogram or predictive model in men with treatment-naïve or common LUTS (73.5%–83.2%) 1127. The predictive model proposed by Kim et al 27 was constructed by a combination of Qmax, PVR volume, and TPV. Notably, De Nunzio et al 11 selected only Qmax and transitional zone volume as independent statistical predictors of BOO in the development of their nomogram.…”
Section: Discussionsupporting
confidence: 56%
“…This weak statistical association may be because the urology clinic‐based study populations do not reflect community or primary care setting populations; it may also be due to the lack of knowledge of how age becomes a principal factor in influencing relationships among urinary symptom score, Q max , and TPV . In addition, prostatic enlargement alone cannot predict the presence of BOO, although TPV is statistically correlated with BOO in pressure‐flow studies .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting published evidence about whether the TZI is associated with urinary symptoms . During the last decade, there have been several reports on IPP and PUA . Chia et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was also confirmed that prostate size is associated with the likelihood of BOO 37 . Flow rate is reduced in many men with symptoms of LUT dysfunction, and the combination of prostate enlargement and reduced flow rate with or without post-void residual is a better predictor of BOO than reported symptoms alone 3840 . Grading of BOO with a pressure flow plot has become standard for elderly males.…”
Section: Men With Lower Urinary Tract Dysfunctionmentioning
confidence: 99%